Dialog Antar Agama di Pondok Pesantren: Membangun Kesadaran Pluralisme dan Toleransi Beragama - Putwaningtyas, Wika Fitriana (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2023)
This article will discuss the theories of Leonard Swidler and Diana Eck on interreligious dialogue, pluralism, and religious tolerance, and how these two theories can be applied in the context of an Islamic boarding school (Pondok Pesantren). Leonard Swidler's theory emphasizes the importance of interreligious dialogue as a communication process involving mutual respect, mutual learning, and mutual transformation in understanding religious beliefs. The collaborative method developed by Swidler can be used as a framework to facilitate dialogue among students in Pondok Pesantren, with the aim of expanding their understanding of other religions and building better religious tolerance. Eck's theory emphasizes the importance of religious pluralism and recognition of religious diversity. Religious pluralism involves respect for the values found in each religion and the development of an active attitude of religious tolerance. Eck's approach can help students in Pondok Pesantren see diversity as something positive, expand their insights into other religions, and strengthen interfaith relationships. In the context of Pondok Pesantren, interreligious dialogue based on Swidler and Eck's theories plays a crucial role in building awareness of pluralism and religious tolerance. Through interreligious dialogue, students can learn to appreciate religious differences, broaden their perspectives, reduce stereotypes and prejudices, and build harmony among different religious communities within the boarding school. By combining the theories of Swidler and Eck, Pondok Pesantren can become a place that promotes inclusive interreligious dialogue, builds awareness of pluralism, and encourages religious tolerance. Interreligious dialogue in Pondok Pesantren plays a significant role in shaping the younger generation to have a better understanding of other religions and to be able to practice the values of pluralism and religious tolerance in their lives.ABSTRAK Tulisan ini akan membahas teori Leonard Swidler dan Diana Eck tentang dialog antaragama, pluralisme, dan toleransi beragama, serta bagaimana kedua teori ini dapat diterapkan dalam konteks Pondok Pesantren. Teori Leonard Swidler menggarisbawahi pentingnya dialog antaragama sebagai proses komunikasi yang melibatkan saling menghormati, saling belajar, dan saling mengubah dalam memahami perbedaan keyakinan agama. Metode kolaboratif yang dikembangkan oleh Swidler dapat digunakan sebagai kerangka kerja dalam memfasilitasi dialog antar santri di Pondok Pesantren, dengan tujuan memperluas pemahaman mereka tentang agama-agama lain dan membangun toleransi beragama yang lebih baik. Teori Eck menekankan pentingnya pluralisme beragama dan pengakuan terhadap keberagaman agama. Pluralisme beragama melibatkan penghormatan terhadap nilai-nilai yang ada dalam masing-masing agama dan pembangunan sikap toleransi beragama yang aktif. Pendekatan Eck dapat membantu para santri di Pondok Pesantren melihat keberagaman sebagai sesuatu yang positif dan memperluas wawasan mereka tentang agama- agama lain, serta memperkuat hubungan antarumat beragama. Dalam konteks Pondok Pesantren, dialog antaragama berdasarkan teori Swidler dan Eck memiliki peran penting dalam membangun kesadaran pluralisme dan toleransi beragama. Melalui dialog antaragama, para santri dapat belajar untuk menghargai perbedaan keyakinan agama, memperluas wawasan mereka, mengurangi stereotip dan prasangka, serta membangun kerukunan antarumat beragama di dalam pesantren. Dengan menggabungkan teori Swidler dan Eck, Pondok Pesantren dapat menjadi tempat yang mempromosikan dialog antaragama yang inklusif, membangun kesadaran pluralisme, dan mendorong toleransi beragama. Dialog antaragama di Pondok Pesantren memainkan peran penting dalam membentuk generasi muda yang memiliki pemahaman yang lebih baik tentang agama-agama lain, serta mampu menjalankan nilai-nilai pluralisme dan toleransi beragama dalam kehidupan mereka.